Siamese-Network-Based Learning to Rank for No-Reference 2D and 3D Image Quality Assessment - Yuzhen Niu (IEEE Access, 2019)
2D image quality assessment (IQA) and stereoscopic 3D IQA are considered as two different tasks in the literature. In this paper, we present an index for both no-reference 2D and 3D IQA. We propose to transform the IQA task into a task of quality comparison between images. By generating image pairs, the amount of training data reaches the square of the original amount of data, effectively solving the lacking of training samples. We also propose a learning to rank model using Siamese convolutional neural networks (LRSN) for quality comparison. The presented LRSN has two branches that have the same structure, share weights with each other, and take two image patches as inputs. The goal of LRSN is learning to rank the quality scores between the two input image patches. The relative quality score of a test image is obtained by first comparing its image patches with many image patches of other images and counts the number of times that its image patches are ranked superior to other patches. The experimental results on three 2D (LIVE, CSIQ, and TID2013) and three 3D (LIVE 3D Phase-I, LIVE 3D Phase-II, and NBU) IQA databases demonstrate that the proposed LRSN model works well for both 2D and 3D IQA and outperforms the state-of-the-art no-reference 2D and 3D IQA metrics.